Development of Swishmax-4 Learning Media in Education Courses and Basic Concepts of Mathematics - Iesyah Rodliyah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2023)
Learning media is needed to help facilitate the process of learning mathematics. The learning media prepared by educators make students more active. In this study the aim was to develop Swishmax-4 learning media in educational subject matter and basic mathematical concepts. The type of research used by researchers is development using the ADDIE model. The results showed that the learning media was in the form of Swishmax-4-assisted interactive questions which referred to the modified research and development design of the ADDIE development model. The results of the expert validation of the developed learning media obtained the category "valid" or suitable for use. In addition, student responses to the learning media that were developed were good. The results of the effectiveness seen from the learning outcomes are included in the effective category, while the results of the practicality test seen from the questionnaire show that the media is practical to use.